High and low doses of clarithromycin treatment are associated with different clinical efficacies and immunomodulatory properties in chronic rhinosinusitis. Issue 3 (March 2014) - Fan, Y; Xu, R; Hong, H; Luo, Q; Xia, W; Ding, M; Shi, J; Lv, M; Li, H
Abstract Background: Low-dose clarithromycin has been recommended for the treatment of chronic rhinosinusitis without nasal polyps. However, it is uncertain whether a high dose of clarithromycin is more effective than a low dose. Methods: Forty-three chronic rhinosinusitis patients were randomised to low-dose or high-dose clarithromycin groups, and clinical efficacy was evaluated. Pre- and post-treatment measures included: nasal symptom assessment, endoscopic inspection (Lund–Kennedy system), a quality of life questionnaire (the Sino-Nasal Outcome Test 20) and examination of cytokine levels (interleukin-5 and -8) in nasal secretions. Results: The high dose of clarithromycin was significantly better in terms of clinical efficacy than the low dose for the treatment of chronic rhinosinusitis (p < 0.025). Significant differences in nasal cytokine levels (interleukin-5 and -8) were also observed between the low-dose and high-dose groups after short-term clarithromycin treatment (p < 0.025). Conclusion: Short-term, high-dose clarithromycin appears to be more effective for the treatment of chronic rhinosinusitis than low-dose clarithromycin.